2018
DOI: 10.1016/j.econmod.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Wage differential between caste groups: Are younger and older cohorts different?

Abstract: Recent literature has provided evidence that a gender and caste-based wage discrimination can exert negative economic impact on a country's development process. Given the enormous contribution of young population to India's workforce, we examine whether there is any caste-based discrimination considering 'demographic' distinction. Using employment and unemployment National Sample Survey data from India for two rounds during the last two decades (1993 and 2010), we find rising wage gap between privileged and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Ignoring this past discrimination may increase the endowment effect of the earnings gap, resulting in an overestimation of differences in human capital. The potential misspecification due to differences in support of the individual characteristics can be accounted with Ñopo's matching algorithm (Arabsheibani et al, 2018). Thus, another decomposition method is used which assumes different probabilistic distributions of comparable individual characteristics including human capital.…”
Section: Methodology: Parametric and Nonparametric Decomposition Of Earnings Gapmentioning
confidence: 99%
“…Ignoring this past discrimination may increase the endowment effect of the earnings gap, resulting in an overestimation of differences in human capital. The potential misspecification due to differences in support of the individual characteristics can be accounted with Ñopo's matching algorithm (Arabsheibani et al, 2018). Thus, another decomposition method is used which assumes different probabilistic distributions of comparable individual characteristics including human capital.…”
Section: Methodology: Parametric and Nonparametric Decomposition Of Earnings Gapmentioning
confidence: 99%
“…Banerjee and Knight (1985) using survey data in Delhi found gross wage difference between scheduled and non-scheduled caste. In similar lines, Arabsheibani et al (2018); Das and Dutta (2007); Madheswaran and Attewell (2007) found caste-based wage gaps in different demographic groups using National Sample Survey (NSS) data. Bhaumik and Chakrabarty (2006) investigated earnings differences across caste groups and between Muslims and Non-Muslims during 1987-1999.…”
Section: Existing Literaturementioning
confidence: 82%
“…Banerjee and Knight (1985) using a survey data in Delhi found gross wage difference between scheduled and non-scheduled caste. In similar lines, Arabsheibani, Gupta, Mishra, and Parhi (2018); Das and Dutta (2007); Madheswaran and Attewell (2007) found caste-based wage gaps in different demographic groups using National Sample Survey (NSS) data. Bhaumik and Chakrabarty (2006) investigated earnings differences across caste groups and between Muslims and Non-Muslims during 1987−99.…”
Section: Existing Literaturementioning
confidence: 82%